IMPLEMENTASI STRATEGI BIMBINGAN DAN KONSELING KOMPREHENSIF DALAM PERENCANAAN KARIR SISWA SMK - Dewi, Riana Kurnia; Akhmad Fajar Prasetya; Wahyu Nanda Eka Saputra; Hardi Santosa (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Career planning is a crucial aspect for vocational high school (SMK) students as it directly relates to their readiness to enter the workforce or continue their education. In reality, many students still experience confusion in determining their career direction due to limited self-understanding and information about job opportunities. This article aims to describe the concept of career planning for SMK students and explain how a comprehensive guidance and counseling (BK) strategy can be systematically implemented to support this process. The comprehensive BK approach integrates foundational services, responsive services, individual planning, and system support through collaboration among schools, families, and the industrial world. The implemented strategies include interest and aptitude assessments, classical career guidance, individual and group counseling, career curriculum development, and continuous evaluation. Structured implementation helps students recognize their potential, explore career options, set realistic goals, and formulate concrete steps toward their chosen careers. Thus, comprehensive BK services are proven relevant for enhancing the readiness and self-confidence of SMK students in making mature career decisions and adapting to the demands of the workforce.